KEKERASAN GENDER DALAM WACANA TAFSIR KEAGAMAAN DI INDONESIA DALAM PERSPEKTIF ISLAM - Marzuki Marzuki (Jurnal Penelitian Humaniora, 2006)
The primary problem in this research is how is the image of the discourse of gender violence in Islam, what factors causing gender violence in Muslims in Indonesia, and what effort can be taken to overcome the problem. The objective of this research, therefore, is to answer above problems. This is a content analysis research. The object of this research is the content of fiqh books showing gender violence, particularly in Uquud Al-Lujjain fi Bayani Hufuq written by Muhammad bin Umar Nawawi al-Banteni well-known as Imam Nawawi. Parts of the book which is related to gender are studied with the perspective of gender equity in Islam as stated in Quran. In analysis, the researcher bases his idea on some Muslim scholars, particularly to the feminist Muslims. From the various views, the researcher finds the interference of the thought leading to the understanding of gender in Islam perspective. The result of the research shows that generally, gender violence occurs in almost all part of the world, including in Indonesia. The gender violence in Indonesia is greatly affected by some fiqh books which are gender-bias. The books affect the minds of their readers’ religion attitude. Among the cause of gender violence in Indonesia, one reason is because of the partial, not comprehensive, textual, not contextual, local-affected interpretations. In consequence, the understanding of gender does not in line with al Quran which concerns on freedom, equity, and justice. Efforts to overcome the gender violence among Muslims are done by reconstructing and reformulating the understanding of the books. Reconstruction begins from the root problem of the interpretation. Reformulation is carried out through understanding verses in AlQuran and Hadith in contextual, interdisciplinary, and comprehensive approach. Therefore, it is hoped that the new understanding will be in line with the principles in Al-Quran showing justice and gender equity.